1990
DOI: 10.1007/bf01806576
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in serum as a possible parameter for assessment of breast disease

Abstract: The level of selenium in blood serum was determined in 33 patients with breast cancer, 13 women with verified mastopathy, and 43 healthy subjects from the Zagreb area. In the second and third quartiles the values of selenium obtained from sick subjects (41-58 micrograms/L) and healthy subjects (73-89 micrograms/L) differed significantly (P less than 0.001). In the group of subjects with mastopathy, serum selenium in the same way ranged from 67-76 micrograms/L and did not differ significantly from the group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Gupta et al (29) also found that plasma Se concentration was decreased in patients with breast cancer but that Se level decreased with the progress of disease. Similar results were found by Piccinnini et al (30) and Krsnjavi and Beker (31) . Willett et al (32) reported that low serum Se levels existed before the cancers developed, thereby increasing a person's risk of developing cancer.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Gupta et al (29) also found that plasma Se concentration was decreased in patients with breast cancer but that Se level decreased with the progress of disease. Similar results were found by Piccinnini et al (30) and Krsnjavi and Beker (31) . Willett et al (32) reported that low serum Se levels existed before the cancers developed, thereby increasing a person's risk of developing cancer.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were found by Piccinnini et al . ( 30 ) and Krsnjavi and Beker ( 31 ) . Willett et al .…”
Section: Discussionmentioning
confidence: 97%